Crime, Street Vendors and the Historical Downtown in Post-Giuliani Mexico City - Reyes, Rodrigo Meneses (International Journal of Criminology and Sociology, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> This article endeavors to go deeply into the recent transformations that have taken place in the regulation of street-level economic and business activities in Mexico City. It draws upon data collected during the course of a three-year research project carried out from 2007 to 2009, a specific timeframe when the urban authority deployed different legal and repressive strategies in order to ‘clean-up’ the streets of the city’s downtown areas, in keeping with the Giuliani Group’s advice. This paper intends to clarify two different dynamics: (a) how the urban authorities went about applying Giuliani’s advice to clean up the streets, and (b) the consequences these initiatives may have on the historical downtown core. My principal task is to offer a tentative insight into whether the incorporation of Giuliani’s repressive approach to urban planning has affected a specific urban space where, for decades, street-level economic, business and trade activities have been intimately interrelated with the creation of a city’s street culture. Research findings suggest that in those countries where street economic activities constitute a die-hard method of eking out one’s sustenance, the relation between order and crime may be more porous and indeterminate than is recognized and acknowledged by the majority of sociolegal studies that have, over the course of time, developed around this topic. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">